1998
DOI: 10.1063/1.120601
|View full text |Cite
|
Sign up to set email alerts
|

A “smarter-cut” approach to low temperature silicon layer transfer

Abstract: Articles you may be interested inHydrogen implantation-induced layer transfer of silicon using direct wafer bonding AIP Conf. Proc. 1512, 690 (2013); 10.1063/1.4791225Effects of hydrogen implantation temperature on ion-cut of silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 7 publications
3
59
0
Order By: Relevance
“…[61] It is known that even at room temperature B and other group III elements in Si can be strongly passivated by H, resulting in the formation of B±H complexes:…”
mentioning
confidence: 99%
“…[61] It is known that even at room temperature B and other group III elements in Si can be strongly passivated by H, resulting in the formation of B±H complexes:…”
mentioning
confidence: 99%
“…The Si-implantation was done prior to the H-implantation and was not followed by a RTA. Tong et al [156] have reported that in B-implanted samples the stress induced by the B-implantation is not the cause for the observed enhancement in surface blistering. For the present samples, which were implanted with a low Si dose, the anticipated strain is low.…”
Section: Blister Formation In the B+h Implanted Samples When The Boromentioning
confidence: 99%
“…At a given annealing duration, a greater reduction is achieved in the annealing temperature required to form surface blisters, when pre-implanted boron is present in the as-implanted state compared to pre-implanted boron electrically activated before the H-ion implantation. [156] In summary, the study has shown that long-range diffusion of hydrogen-implanted into n-type silicon takes place for an annealing temperature of 390 °C. The presence of a preimplanted boron profile, at depths greater than the implanted hydrogen profile, and the long-range hydrogen diffusion it caused did however not induce an Ion-Cut shift towards larger depths.…”
Section: The Influence Of Boron At Interstitial Lattice Sites On Hydrmentioning
confidence: 99%
See 1 more Smart Citation
“…This wafer-scale ultra-microtomy is usually referred to as exfoliation or``smart cut''. However, strictly speaking Smart Cut 1 refers to a proprietary process sequence, and alternative suggestions as to how to realise the layer splitting have been demonstrated successfully [27]. The principle behind Bruel's idea is deceptively simple (Fig.…”
Section: Ion Beam Cuttingmentioning
confidence: 99%